2016
DOI: 10.1080/15412555.2016.1239703
|View full text |Cite
|
Sign up to set email alerts
|

Which is the Best Screening Strategy for COPD among Smokers in Primary Care?

Abstract: We developed a questionnaire to detect cases of chronic obstructive pulmonary disease (COPD) and compared its reliability with other strategies. In order to develop the new questionnaire (COPD screening questionnaire from Terrassa [EGARPOC]) we used data from an epidemiological study on the prevalence of COPD in smokers and calculated the odds ratio for each variable showing significance for the diagnosis of COPD on regression analysis. For comparison among questionnaires and the portable spirometer COPD-6, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…The correlation of FEV 1 to FVC in the current study was striking as they report a correlation coefficient of 0.9; moreover, as previously reported, FVC is prognostic of survival (10). It is interesting to note that as FEV 1 and FEV 1 /FVC are nearly equivalent in terms of identification of obstruction, association to exacerbation and dyspnea and the same is most certainly the case for FVC and by extension FEV 6 (14). Why is this important?…”
supporting
confidence: 59%
“…The correlation of FEV 1 to FVC in the current study was striking as they report a correlation coefficient of 0.9; moreover, as previously reported, FVC is prognostic of survival (10). It is interesting to note that as FEV 1 and FEV 1 /FVC are nearly equivalent in terms of identification of obstruction, association to exacerbation and dyspnea and the same is most certainly the case for FVC and by extension FEV 6 (14). Why is this important?…”
supporting
confidence: 59%
“…The study included 1738 subjects over the age of 45 with a history of smoking and found a rate of underdiagnosis of 73%. Recently, the same group performed a case-finding study in smokers or former smokers older than 40 years and found a prevalence of COPD of 26.7%, with the majority of patients being in GOLD stages I and II (42.1 and 49.1%, respectively) [ 21 ]. Up to 29% of patients with underdiagnosed COPD are asymptomatic [ 22 ], which contributes to late detection.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…In addition, patients often under-recognize the significance of respiratory symptoms, or they may accept that their symptoms are caused by smoking and ignore them rather than consult. Another cause for underdiagnosis might also be a deficient active search for COPD by health care professionals [ 21 ]. Some of the diagnostic initiatives that have been tested to improve COPD diagnosis are early detection programs [ 23 ] and other tools such as the use of peak-flow meters or mini spirometers [ 24 ], and screening questionnaires [ 21 , 25 ].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…Studies that focussed on screening (i.e., case finding) for COPD found microspirometry to be a valid method and significantly better than using screening questionnaires. 10 , 13 15 But what if microspirometry is used in routine general practice settings as a POC test for COPD? This could potentially reduce underdiagnosis of COPD while avoiding the need for screening initiatives to identify missed COPD cases in primary care populations.…”
Section: Introductionmentioning
confidence: 99%